2019
DOI: 10.26425/2658-3445-2019-3-64-72
|View full text |Cite
|
Sign up to set email alerts
|

Statistical study of students’ digital competencies

Abstract: Currently, there is a tendency of rapid development of information and communication technologies and their implementation into the сountry`s economy and life of the society. The purpose of this article was to study the digital competencies of students at different levels of education, as well as their comparison with digital competencies of employed in the economy. The article considers the projects and strategies developed and implemented by the European Union and the Russian Federation in order to reform th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 3 publications
0
4
0
1
Order By: Relevance
“…The study sample consisted of (20) fourth-grade students with dysgraphia. They were randomly divided into two groups: a control group with (10) members and an experimental group with (10) members; the study tool was Ray's Visual Perception Test (2018), Shoshoni Writing Test (2019), John Raven's Intelligence Test (2016), and the training program that was prepared, the study indicated that there were statistically significant differences in writing skills between the average results of the control group and the results of the experimental group in the posttest in favor of the experimental group.…”
Section: Previous Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…The study sample consisted of (20) fourth-grade students with dysgraphia. They were randomly divided into two groups: a control group with (10) members and an experimental group with (10) members; the study tool was Ray's Visual Perception Test (2018), Shoshoni Writing Test (2019), John Raven's Intelligence Test (2016), and the training program that was prepared, the study indicated that there were statistically significant differences in writing skills between the average results of the control group and the results of the experimental group in the posttest in favor of the experimental group.…”
Section: Previous Studiesmentioning
confidence: 99%
“…Journal of learning disabilities, 51(6), ‫.426-216‬ 17. Morgan, P. L., Farkas, G., Hillemeier, M. M., Pun, W. H., & Maczuga, S (2019)…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The transition to a digital economy requires a change in a key element -education. Consequently, the formation of digital competence is becoming one of the most important tasks of the vocational education system [Dolgikh, Pershina, 2019]. Universal digital competence is introduced into educational standards, which makes it possible to acquire knowledge, skills and abilities, enabling graduates to use information resources and information and communication technologies to achieve goals related to professional activities and active participation in the life of modern society.…”
Section: Introductionmentioning
confidence: 99%